Herpes Zoster Recurrence: A Narrative Review of the Literature - Raunak Parikh; O'Mareen Spence; Nikolaos Giannelos; Iain Kaan (Adis, Springer Healthcare, 2024)
Abstract Introduction Herpes zoster (HZ; shingles) is a painful, cutaneous disease caused by reactivation of the varicella zoster virus, which causes varicella (chickenpox) typically during childhood. The considerable healthcare burden of HZ is relatively well documented, with approximately one in three individuals experiencing at least one episode during their lifetime, debilitating symptoms including neuropathic pain, and complications such as post-herpetic neuralgia, vision loss, and rarely, stroke, and increased severity in immunocompromised individuals. However, we are not aware of a comprehensive review of literature specifically examining the burden of HZ recurrence. Methods We conducted a PubMed search (1 January 2003-2 February 2023) to assess available literature on the incidence, risk factors, and clinical features of HZ recurrence. Results The incidence of HZ recurrence reported by the studies identified was wide ranging. Studies in general populations of immunocompetent or immunocompetent/immunosuppressed (mixed) populations with an initial HZ episode estimate that approximately 1.2-9.6% of individuals may experience HZ recurrence, with an incidence rate of 1.7-16.6 cases per 1000 person-years. HZ recurrence was reported in 0.0-18.2% of immunocompromised individuals with HZ, with an incidence rate of 17.0-55 cases per 1000 person-years. Incidence rates varied according to study design, follow-up, and study populations. Recognized risk factors for HZ recurrence include immunocompromised status, female sex, family history, and comorbidities such as diabetes. Other factors that may predispose individuals to recurrence include long-lasting pain after the initial HZ episode and the presence of herpes zoster ophthalmicus. Discussion Our review underlines that following an initial HZ episode, individuals remain at risk of HZ recurrence, adding to the disease burden in a population. As HZ is preventable by vaccination, national HZ vaccination recommendations should include the need for and timing of vaccination in both immunocompetent and immunocompromised individuals who have a history of HZ.